2023
DOI: 10.1177/23779608231160473
|View full text |Cite
|
Sign up to set email alerts
|

Creative Art Therapy for Improving Depression, Anxiety, and Stress in Patients with Stroke: A Quasi-Interventional Study

Abstract: Introduction Creative art therapy is a psychotherapeutic approach used to enhance the mental health status of patients. Objectives This study aimed to evaluate the effect of creative art therapy on the levels of depression, anxiety, and stress in Jordanian patients following stroke. Methods One-group pretest–posttest design was used; it included four sessions of creative art therapy which were conducted as two sessions for two weeks. This study recruited 85 participants who were within three months poststroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Art therapy is a pristine area in Jordanian Universities (Alwledat et al, 2023); hence, this discipline could gain momentum through tertiary educational institutions. Also, scholars are invited to conduct a wide range of studies with different methodologies to achieve good levels of reliability and validity in the application of this discipline among collectivist communities.…”
Section: Discussion Conclusion Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Art therapy is a pristine area in Jordanian Universities (Alwledat et al, 2023); hence, this discipline could gain momentum through tertiary educational institutions. Also, scholars are invited to conduct a wide range of studies with different methodologies to achieve good levels of reliability and validity in the application of this discipline among collectivist communities.…”
Section: Discussion Conclusion Suggestionsmentioning
confidence: 99%
“…that currently, Alwledat et al (2023) reported that using creative art therapy is important in the rehabilitation process for chronic diseases, such as depression, anxiety, and stress in patients with stroke.…”
Section: Isra Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the present study was consistent with Kongkasuwan et al, 37 studied the effectiveness of creative art therapy on depression in 118 stroke patients, revealing that subjects who attended an artwork program twice a week for four weeks in addition to conventional therapy experienced significantly lower depression than those who received conventional rehabilitation alone. Furthermore, several studies 15,22,[37][38][39][40][41] demonstrated that participating in art activities helped with relaxation, self-esteem, inspiration, and distraction in a stressful rehabilitation environment, which could lead to less depression in stroke patients. Gangwani et al 42 identified factors affecting post-stroke recovery that self-esteem, and motivation could promote good rehabilitation outcomes.…”
Section: Depressionmentioning
confidence: 99%
“…Gangwani et al 42 identified factors affecting post-stroke recovery that self-esteem, and motivation could promote good rehabilitation outcomes. Alwledat, et al 38 studied the effects of two sessions per week, 1.5 hours per session, for two weeks of creative art therapy on depression, anxiety, and stress on 85 stroke patients, which demonstrated that art activities could significantly reduce depression, anxiety, and stress in these participants.…”
Section: Depressionmentioning
confidence: 99%